The crystal structure of 2,4,4-triphenyl-4H-benzo[b][1,4]oxaphosphinin-4-ium bromide – dichloromethane (1/1), C27H22BrCl2OP - Liu Fen; Sun Longgen; Huang Haiyang (Zeitschrift für Kristallographie - New Crystal Structures)
C27H22BrCl2OP, monoclinic, P21/c (no. 14), a = 9.0066(2) Å, b = 15.4924(4) Å, c = 18.5110(4) Å, β = 95.487(2)°, V = 2571.06(11) Å3, Z = 4, R gt(F) = 0.0509, wR ref(F 2) = 0.1494, T = 296 K.